Systemic rapamycin to prevent in-stent stenosis in peripheral pulmonary arterial disease: early clinical experience. (28th December 2015) - Hallbergson, Anna; Esch, Jesse J.; Tran, Trang X.; Lock, James E.; Marshall, Audrey C.
Abstract: Objectives: We have taken a novel approach using oral rapamycin – sirolimus – as a medical adjunct to percutaneous therapy in patients with in-stent stenosis and high risk of right ventricular failure. Background: Peripheral pulmonary artery stenosis can result in right ventricular hypertension, dysfunction, and death. Percutaneous pulmonary artery angioplasty and stent placement acutely relieve obstructions, but patients frequently require re-interventions due to re-stenosis. In patients with tetralogy of Fallot or arteriopathy, the problem of in-stent stenosis contributes to the rapidly recurrent disease. Methods: Rapamycin was administered to 10 patients (1.5–18 years) with peripheral pulmonary stenosis and in-stent stenosis and either right ventricular hypertension, pulmonary blood flow maldistribution, or segmental pulmonary hypertension. Treatment was initiated around the time of catheterisation and continued for 1–3 months. Potential side-effects were monitored by clinical review and blood tests. Results: Target serum rapamycin level (6–10 ng/ml) was accomplished in all patients; eight of the nine patients who returned for clinically indicated catheterisations demonstrated reduction in in-stent stenosis, and eight of the 10 patients experienced no significant side-effects. Among all, one patient developed diarrhoea requiring drug discontinuation, and one patient experienced gastrointestinal bleeding while on therapy that was likely due to an indwelling feeding tube and this patient tolerated rapamycin well following tube removal. Conclusions: Our initial clinical experience supports that patients with peripheral pulmonary artery stenosis can be safely treated with rapamycin. Systemic rapamycin may provide a novel medical approach to reduce in-stent stenosis.